4х^2 - 3х = 3(12 - х) ? х^2 - 3х = 2( 12 -х ) - х ? -х^2 +6х = 2( 12 + 2х) +2х ?

0 голосов
28 просмотров

4х^2 - 3х = 3(12 - х) ? х^2 - 3х = 2( 12 -х ) - х ? -х^2 +6х = 2( 12 + 2х) +2х ?


Алгебра (26 баллов) | 28 просмотров
Дан 1 ответ
0 голосов

1. 4х² - 3х = 3 ( 12 - х )
4х² - 3х = 36 - 3х
4х² - 3х + 3х = 36
4х² = 36
х² = 9
х = ±3.
Ответ : х = ±3.

2. х² - 3х = 2 ( 12 - х ) - х
х² - 3х = 24 - 2х - х
х² - 3х + 2х + х = 24
х² = 24
х = ± √24.
Ответ : х = ± √24.

3. -х² + 6х = 2 ( 12 + 2х ) + 2х
-х² + 6х = 24 + 4х + 2х
-х² + 6х - 4х - 2х = 24
-х² = 24
х² = -24.
Ответ : нет решений.
Нет решений, так как нет такого числа, квадрат которого равен отрицательному числу.

Удачи))))

(14.9k баллов)